Genetic diversity of Dillenia indica using iPBS markers and its implications for sustainability management in Koh Kret, Thailand - ATIYA RATTANAPITTAYAPRON; ONGKARN VANIJAJIVA; ROMAIN SCALONE; XUA GUO; DECH BOONPRAJAK (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Rattanapittayapron A, Vanijajiva O, Scalone R, Guo X, Boonprajak D. 2026. Genetic diversity of Dillenia indica using iPBS markers and its implications for sustainability management in Koh Kret, Thailand. Biodiversitas 27 (3): d270306. https://doi.org/10.13057/biodiv/d270306. Protecting genetic diversity in perennial fruit trees is essential for maintaining healthy ecosystems and supporting local communities under increasing urbanization. Dillenia indica is a culturally important fruit species on Koh Kret, Nonthaburi Province, Thailand, yet it has not previously been investigated using molecular markers. This study assessed the genetic diversity and population structure of D. indica using inter-Primer Binding Site (iPBS) markers together with information on local cultivation practices. A total of 82 individuals were sampled from seven villages across the island. Twenty iPBS primers generated 88 clear and reproducible bands, of which 39 (44.32%) were polymorphic, with a mean Polymorphism Information Content (PIC) of 0.209. Genetic diversity indices indicated moderate variation (H = 0.138±0.032, I = 0.270±0.307). Analysis of molecular variance showed that most genetic variation occurred within populations (78%), whereas 22% was distributed among populations (ΦST = 0.224, p<0.001). Neighbor-Joining clustering, principal coordinate analysis, and Bayesian inference consistently identified two genetic groups (K = 2) with high levels of admixture, suggesting considerable gene flow and weak spatial structuring. Interviews with local growers revealed that seed exchange, mixed home-garden cultivation, and natural regeneration contribute to genetic connectivity among communities. This research provides the first molecular evidence for D. indica on Koh Kret and demonstrates that traditional management practices help maintain intra-population genetic diversity. The findings support community-based conservation and sustainable utilization of this species within peri-urban agroecosystems.